Do antisaccade deficits in schizophrenia provide evidence of a specific inhibitory function? - GARAVAN, HUGH PATRICK; ROBERTSON, IAN; CORVIN, AIDEN PETER; MORRIS, DEREK WILLIAMS; DONOHOE, GARY (JAMES) (Cambridge University Press, 2006)
Background: Despite its inhibitory control requirements, antisaccade deficits have been consistently associated with working memory impairments in schizophrenia. We investigated whether variance in antisaccade per formance could be better accounted for in terms of a specific inhibitory function. Method: We assessed 48 clinically stable out-patients with schizophrenia on an antisaccade task, as well as on measures of spatial and verbal working memory, sustained selective attention, and a simple motoric go 0 no-go measure of response inhibition. Results: In a stepwise multiple regression analysis, go 0 no-go task per formance accounted for a considerably greater percentage of variance in antisaccade per formance (25.3%) than either working memory (8.4%) or sustained selective attention task (9.1%). Discussion: We conclude that antisaccade deficits in schizophrenia appear to be better understood in terms of a specific deficit of inhibitory control than in terms of more general difficulties with context maintenance or goal neglect.
PUBLISHED
Keywords: Psychology